Caregiver Emotional Support on Adolescent Self-Concept at Saadatul Banaat Orphanage Bulukumba - Rukiana Novianti Putri; Bahrul Amsal; Rahayu Rahayu (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to describe the impact of caregivers' emotional support on the self-concept of adolescents at the Saadatul Banaat orphanage in Bulukumba. This study used a descriptive qualitative method in the form of written narratives from the research subjects and observed behavior. In this study, the researchers determined the research location to be the Saadatul Banaat orphanage in Bulukumba District, South Sulawesi. The results showed that the emotional support of caregivers affected the self-concept of adolescents at the Saadatul Banaat Bulukumba orphanage, where adolescents found it easier to accept their situation, believe in their abilities, have a positive image of themselves, and have a desire to develop self-confidence in interactions so that they are optimistic about developing their potential.